Diamond and carbon nanostructures for biomedical applications. Issue 1 (2nd January 2021) - Xue, Yuxiang; Feng, Xue; Roberts, Samuel C.; Chen, Xianfeng
Abstract: Diamond and carbon nanostructures possess outstanding advantages, such as chemical inertness, stable fluorescence, tunable surface characteristics and excellent biocompatibility. In particular, diamond has extremely strong mechanical properties, and therefore the nanostructures have been developed for unique applications. Herein, we systematically review the very recent applications of these structures in drug delivery, bioimaging and biosensing, followed by discussion of their advantages, limitations and challenges in translation to potential clinical applications and presentation of our insights of their future development.